Analysis of Road Safety in terms of Management and Traffic Safety in Palembang (Case Study of Colonel H. Burlian Road, Palembang) - Byllardo, Andriyan Agiyah; Andarini, Desheila; Novrikasari, Novrikasari; Lestari, Mona; Camelia, Anita; Utama, Feranita; Andarwiza, Siti Noverizky (Jurnal Penelitian Transportasi Darat, 2023)
Road traffic accidents are the ninth leading cause of death and are responsible for 2.2% of all deaths globally. Road safety audits are one way to anticipate traffic accidents. These accidents generally occur due to various causes collectively, including: humans, road conditions, and road completeness. The objective of this study is to conduct a Road Safety Analysis in the Management and Traffic Safety Aspects of Kolonel H. Burlian Street in Palembang. The research used a descriptive method with a qualitative approach as well as interview methods and HIRARC analysis. There are six informants with two main informants and four regular informants. The results showed that along the Kolonel H. Burlian Street, the road geometry was still not suitable for vehicles due to the road conditions that had many holes to the bumps, the completeness of traffic signs was sufficiently fulfilled because they had poor conditions such as road markings in faded conditions or covered with patches.